Melatonin activity and receptor expression in endometrial tissue and endometriosis. Issue 7 (18th June 2019) - Mosher, A A; Tsoulis, M W; Lim, J; Tan, C; Agarwal, S K; Leyland, N A; Foster, W G
Abstract: STUDY QUESTION: Are melatonin receptors (melatonin receptor 1A (MR1A) and melatonin receptor 1B (MR1B)) expressed in human endometrium and endometriotic tissue, and does melatonin affect endometrial cell proliferation? SUMMARY ANSWER: Melatonin receptors are expressed in human eutopic endometrium, endometriomas and peritoneal lesions, although to different extents, and melatonin treatment attenuated estradiol-induced endometrial epithelial cell proliferation in culture. WHAT IS KNOWN ALREADY: Melatonin decreased endometriotic lesion volume in a rat model of endometriosis. Melatonin treatment reduced pain scores in and analgesic use by women with endometriosis. STUDY DESIGN, SIZE, DURATION: Basic science study using human endometrial tissue and an endometrial epithelial cell line. PARTICIPANTS/MATERIALS, SETTING, METHODS: Measurement of melatonin receptor expression (mRNA and protein) in women with surgically confirmed endometriosis (endometrioma ( n = 20) or peritoneal lesion ( n = 11) alone) and women without surgical evidence of endometriosis (control, n = 15). Collection of endometrial and endometriotic tissue samples, gynecologic history and demographic information. Quantification of estradiol (1.0 nM) and melatonin (0.1 nM–1.0 μM) ± estradiol-induced endometrial epithelial cell proliferation in cultures of endometrial epithelial cells (CRL-1671) following 24 and 48 hours of culture. MAIN RESULTS AND THE ROLE OF CHANCE: MR1A and MR1B were localized by immunohistochemistry in glandular epithelial cells of endometrial biopsies from women with and without endometriosis. Both receptors were expressed in eutopic and ectopic endometrial tissue. mRNA expression of MR1A and MR1B was significantly greater in peritoneal lesions than in either endometriomas or eutopic endometrium. However, protein expression of MR1A was decreased in peritoneal lesions compared to control eutopic endometrium, whereas MR1B expression did not differ between the groups. Melatonin (0.1 nM–1.0 μM) treatment inhibited estradiol (1.0 nM)-induced endometrial epithelial cell proliferation at 48 hours but not 24 hours of culture. LIMITATIONS, REASONS FOR CAUTION: Beneficial effects of melatonin seen in culture have yet to be comprehensively evaluated in women with endometriosis. WIDER IMPLICATIONS OF THE FINDINGS: Our data suggest that melatonin may be useful as an adjunct to current endometriosis treatments. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Canadian Institutes of Health Research (grant MOP142230 to W.G.F.). A.A.M. is supported by a resident research grant through the Physicians Services Incorporated Foundation. The authors have no conflicts of interest.